Experimental characterisation of bagasse biomass material for energy production (2014)
A number of persistent problems have been associated with the supply of traditional domestic fuel products in Nigeria particularly in rural areas including deforestation, wood-fuel shortage and high cost of fossil fuel. The use of bio-fuels from agricultural waste biomass which are usually available in large quantities was advocated. This paper therefore presents the experimental determination of fuel performance parameters of sugarcane bagasse after two weeks of sun drying. Samples were prepared and analysed for bulk density, moisture content, ash content, volatile matter, chemical and calorific values. The results indicate that fuel performance properties are affected by moisture content. The bulk density and volatile matter decrease with decrease in moisture content. After 14 days of drying; the moisture content, bulk density and the volatile matter decreased from 30%; 320kg/m3 and 81.7% to 7%, 280kg/m3 and 69.4% respectively. The ash contents, carbon contents and the calorific values increased from 3.30%; 12%; and 5.57 MJ/kg to 7.21%, 16% and 14 MJ/kg respectively. The proximate analyses results and mineral elements in bagasse were in agreement with those found in wood-fuel. The results suggest that the disposed off bagasse could be developed as a source of energy for domestic and industrial purposes.